Drugs for treating myocardial fibrosis - Ren, Zhanhong; Zhang, Zixuan; Ling, Li; Liu, Xiufen; Wang, Xin (Frontiers in Pharmacology, 2023)
Myocardial fibrosis, which is a common pathological manifestation of many cardiovascular diseases, is characterized by excessive proliferation, collagen deposition and abnormal distribution of extracellular matrix fibroblasts. In clinical practice, modern medicines, such as diuretic and β receptor blockers, and traditional Chinese medicines, such as salvia miltiorrhiza and safflower extract, have certain therapeutic effects on myocardial fibrosis. We reviewed some representative modern medicines and traditional Chinese medicines (TCMs) and their related molecular mechanisms for the treatment of myocardial fibrosis. These drugs alleviate myocardial fibrosis by affecting related signaling pathways and inhibiting myocardial fibrosis-related protein synthesis. This review will provide more references and help for the research and treatment of myocardial fibrosis.